Clinical care of the diabetic foot - Armstrong, David G.; Lavery, Lawrence A. (American Diabetes Association, 2016)
The third edition of Clinical Care of the Diabetic Foot has been fully revised and updated, and continues to be the essential handbook on foot care and the treatment of the diabetic foot.The diabetic foot is typically the victim of nerve damage, micro- and macrovascular disease, and faulty healing, mechanisms that without proper care can lead to amputation.